Sensory Abnormalities in Autism Spectrum Disorders: A Focus on the Tactile Domain, From Genetic Mouse Models to the Clinic - Balasco, Luigi; Provenzano, Giovanni; Bozzi, Yuri (Frontiers in Psychiatry, 2020)
Sensory abnormalities are commonly recognized as diagnostic criteria in autism spectrum disorder (ASD), as reported in the last edition of the Diagnostic and Statistical Manual of Mental Disorder (DSM-V). About 90% of ASD individuals have atypical sensory experiences, described as both hyper- and hy-po-reactivity, with abnormal responses to tactile stimulation representing a very frequent finding. In this review, we will address the neurobiological bases of sensory processing in ASD, with a specific focus of tactile sensitivity. In the first part, we will review the most relevant sensory abnormalities detected in ASD, and then focus on tactile processing deficits through the discussion of recent clinical and experi-mental studies. In the search for the neurobiological bases of ASD, several mouse models have been gen-erated with knockout and humanized knockin mutations in many ASD-associated genes. Here we will therefore give a brief overview of the anatomical structure of the mouse somatosensory system, and de-scribe the somatosensory abnormalities so far reported in different mouse models of ASD. Understand-ing the neurobiological bases of sensory processing in ASD mouse models may represent an opportunity for a better comprehension of the mechanisms underlying sensory abnormalities, and for the development of novel effective therapeutic strategies.